2013
DOI: 10.1021/jp311986m
|View full text |Cite
|
Sign up to set email alerts
|

A Surface-Specific Isotope Effect in Mixtures of Light and Heavy Water

Abstract: Isotope fractionation between different phases is a subtle but very important phenomenon that is related to the quantum nature of light nuclei, and that has important consequences for geochemistry, hydrology, and biology. Here we present a joint experimental/theoretical investigation of the differential segregation of hydrogen and deuterium at the liquid/vapor interface of mixtures of light and heavy water. We use both vibrational sum-frequency spectroscopy and path integral molecular dynamics simulations to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 56 publications
4
72
1
4
Order By: Relevance
“…Although the competition between intra-and intermolecular quantum effects that appears to be ubiquitous in water reduces the impact of neglecting NQEs on average properties (9,25,32,33), the protons should always be treated as quantum particles in studies aimed at capturing rare events or, more generally, properties that depend on the tail of the equilibrium distribution. For instance, a recent study (34) suggests that conflicting interpretations of the X-ray absorption spectroscopy of water (35,36) can be reconciled based on the presence of asymmetrical configurations of HBs in water.…”
Section: Discussionmentioning
confidence: 99%
“…Although the competition between intra-and intermolecular quantum effects that appears to be ubiquitous in water reduces the impact of neglecting NQEs on average properties (9,25,32,33), the protons should always be treated as quantum particles in studies aimed at capturing rare events or, more generally, properties that depend on the tail of the equilibrium distribution. For instance, a recent study (34) suggests that conflicting interpretations of the X-ray absorption spectroscopy of water (35,36) can be reconciled based on the presence of asymmetrical configurations of HBs in water.…”
Section: Discussionmentioning
confidence: 99%
“…Now, let us consider how the direct estimators can be used in a setting in which one cannot define a clear-cut distinction between the A and B states, but has just one system described by a potential V , and the two states are different regions of configuration space, that are associated to two characteristic functions θ A (q) and θ B (q), which are one if the configuration can be ascribed to one of the states, and zero otherwise. For instance, the functions could select configurations in which the tagged atom is at a given distance from an interface [62], or in a specific hydrogen-bonding environment.…”
Section: Discussionmentioning
confidence: 99%
“…However,acombined theoretical and experimental study of the free O À H/O À Dg roups at the water-air interface has shown that the bond orientation of the water molecules at this interface depends on the isotopic dilution which is caused by nuclear quantum effects. [137,138] Path integral MD simulations at the waterair interface revealed the preferential orientation of the O À H and O À Dgroups of the HDO molecule.The average orientational angle between the OÀH(O À D) groups and the surface normal is displayed in Figure 13 b. Thes imulated and experimental SFG data confirmed that the OÀHg roup of an HDO molecule is slightly more oriented toward the air and is less inclined to engage in hydrogen bonds with other water molecules (Figure 13 c). These give rise to the zero-point energy of the vibrational mode,influencing the hydrogen-bonding strength in ac omplex manner.N uclear quantum effects are particularly relevant for the interface,b ecause the vibrational energy difference between the free OÀHand hydrogen-bond O À Hstretch mode is comparable to kT at room temperature.…”
Section: Nuclear Quantum Effectsmentioning
confidence: 99%